2009
DOI: 10.1177/039463200902200222
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Hyaluronic Acid Injection in Carpometacarpal Osteoarthritis: Short-Term Results

Abstract: Carpometacarpal osteoarthritis (CMC-OA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 22 publications
0
23
0
4
Order By: Relevance
“…This initial report was not blinded and had not control group; a small decrease in pain was noted but no statistical values were reported. Recently, Salini et al 18 showed that pain at rest and during activity decreased from 1.8 to 0.5 (p<0,001) and from 8.05 to 4.15 (p<0,001), respectively. In other studies once weekly injection for 3 weeks with moderate TMCJ OA (K-L 2-3 grades) showed significant improvements in disabilities of the hand score and pain at 26 weeks, but key and opposition pinch showed minimal differences compared with baseline 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This initial report was not blinded and had not control group; a small decrease in pain was noted but no statistical values were reported. Recently, Salini et al 18 showed that pain at rest and during activity decreased from 1.8 to 0.5 (p<0,001) and from 8.05 to 4.15 (p<0,001), respectively. In other studies once weekly injection for 3 weeks with moderate TMCJ OA (K-L 2-3 grades) showed significant improvements in disabilities of the hand score and pain at 26 weeks, but key and opposition pinch showed minimal differences compared with baseline 4 .…”
Section: Discussionmentioning
confidence: 99%
“…HA in osteoarthritis has been widely studied in large joints as a symptom-modifying treatment for its potential to restore synovial fluid viscoelastic properties, and it may also have modifying effects on diseased joints [17][18][19] . In experimental models of OA, HA treatment showed positive long lasting effects, possibly mediated by the reduction of inflammatory mediators and effects on molecular factors involved in disease progression 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In our experience (Table 4), a single ultrasound guided injection of hyaluronic acid is effective in treatment of carpo -metacarpal osteoarthritis (Salini et al, 2009). After therapy the Visual Analogic Scale pain score, both at rest and during common daily activities, decreases, while the hand function and strength are improved.…”
Section: Carpo -Metacarpal Osteoarthritismentioning
confidence: 92%
“…In quite all the clinical trials, no general side effects were observed, and only few patients reported a sensation of heaviness and pain in their joint after injection (Abate M, 2009). These effects were more frequent in studies performed in blind conditions compared to those performed under imaging guidance.…”
Section: Side Effectsmentioning
confidence: 99%
“…Several papers showed that US can be applied in the monitoring of the response to treatment with hyaluronic acid in patients affected with OA. 58,59 Recently, we described the employment of US in the assessment of 53 patients with primary symptomatic knee OA treated for 12 consecutive days with locally applied mud-packs. We observed a significant improvement of the US findings evaluated with a semiquantitative score, that correlated with clinical and laboratory indexes of disease activity.…”
Section: Us In Degenerative Rheumatic Diseasementioning
confidence: 99%